Pathological outcomes of HER2‐positive non‐metastatic breast cancer patients treated with neoadjuvant dual anti‐HER2 therapy and taxane: An Australian experience. Issue 3 (19th June 2019) - Choi, Joseph Do Woong; Hughes, Thomas Michael D.; Marx, Gavin; Rutovitz, Josie; Hasovits, Csilla; Ngui, Nicholas K.
Abstract: Aims: Internationally, there has recently been growing interest in the use of neoadjuvant pertuzumab and trastuzumab in patients with non‐metastatic HER‐2 positive breast cancer following the NEOSPHERE trial in 2012. However, pertuzumab is currently not funded by the Pharmaceutical Benefits Scheme (PBS) in Australia for use in this setting. The authors sought to assess the clinical and pathological response rates at the time of surgery in patients who received neoadjuvant dual anti‐HER2 and taxane therapy in a multidisciplinary breast cancer unit. Methods: A retrospective case series of all patients treated with the neoadjuvant therapy, and who had definitive surgery was conducted. Demographic data, size, grade, tumor type, receptor status prior to neoadjuvant treatment, pathological complete response (pCR) rates, and adverse effects were analyzed. Results: Nineteen patients were included in the study. Sixty‐eight percent of all patients achieved pCR, of which 54% further demonstrated no residual ductal carcinoma in situ. Eight patients (42%) had N1 disease pretreatment, of these 88% demonstrated total pCR in the axilla and the breast. Most adverse effects to treatment were manageable grade 1–2 side effects. Conclusion: This is the first reported Australian experience using neoadjuvant dual anti‐HER2 and taxane therapy for HER‐2 positive nonmetastatic breast cancer. The authors have demonstrated favorable pCR rates for invasive disease compared to the NEOSPHERE trial (68% vs 46%), with reasonable patient tolerability. Larger collaborative data sets are required to fully evaluate correlation of pCR with survival outcomes, and cost‐effectiveness. National funding models need to be considered.